2021
DOI: 10.1021/acs.jmedchem.0c01002
|View full text |Cite
|
Sign up to set email alerts
|

GPR120/FFAR4 Pharmacology: Focus on Agonists in Type 2 Diabetes Mellitus Drug Discovery

Abstract: The G-protein coupled receptors (GPCRs) activated by free fatty acids (FFAs) have emerged as new and exciting drug targets, due to their plausible translation from pharmacology to medicines. This perspective aims to report recent research about GPR120/FFAR4 and its involvement in several diseases, including cancer, inflammatory conditions, and central nervous system disorders. The focus is to highlight the importance of GPR120 in Type 2 diabetes mellitus (T2DM). GPR120 agonists, useful in T2DM drug discovery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 135 publications
0
38
0
Order By: Relevance
“…TAK-875 had shown promising efficacy and significantly reducing HbA1C levels without causing any hypoglycemic episodes. However, during phase 2 clinical trials the compound was found to cause liver toxicity and further development of the drug was discontinued [60,61]. Efforts are on to develop safer alternatives with good efficacy and with no or little toxicity [16,20,62].…”
Section: Ffar Agonists In the Treatment Of Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…TAK-875 had shown promising efficacy and significantly reducing HbA1C levels without causing any hypoglycemic episodes. However, during phase 2 clinical trials the compound was found to cause liver toxicity and further development of the drug was discontinued [60,61]. Efforts are on to develop safer alternatives with good efficacy and with no or little toxicity [16,20,62].…”
Section: Ffar Agonists In the Treatment Of Metabolic Diseasesmentioning
confidence: 99%
“…TUG-891 was also able to induced phosphorylation of FFAR4 followed by receptor internalization. TUG-891 was able to mimic almost all the beneficial properties of natural agonists of FFAR4 including GLP-1 secretion from enteroendocrine cells, augmenting glucose uptake in murine adipocytes and inhibiting inflammatory mediators from macrophages [60,66,69]. TUG-891 was also shown to reduce food intake, enhance insulin signaling and reverse insulin resistance in mice.…”
Section: Ffar Agonists In the Treatment Of Metabolic Diseasesmentioning
confidence: 99%
“…Ever since the members of the FFAR family were de-orphanized, their role in different biological processes has been extensively studied. In particular, their contribution to metabolic and energy homeostasis has been comprehensively recognized, and they have attracted considerable attention in the drug discovery field [ 56 , 57 , 58 , 59 ]. As a result, several ligands of FFARs have been developed to use as therapeutic drugs for metabolic diseases like diabetes and obesity.…”
Section: Ffar Agonists In the Treatment Of Metabolic Diseasesmentioning
confidence: 99%
“…1 ). 17 Polar groups are generally carboxylic acids, which play an important role in agonistic activity. TUG-891, the first potent and selective GPR120 agonist, developed at the University of Southern Denmark has been widely used to explore the physiological function of GPR120.…”
Section: Introductionmentioning
confidence: 99%